Changes in preservice teacher dispositions during a teacher preparation program - Kyle LaPaglia; Judy R. Wilkerson (International Journal of Evaluation and Research in Education (IJERE), 2023)
Although substantial attention is being paid nationally to the assessment of pre-service teacher dispositions, largely to meet accreditation requirements, little is known about the extent to which standards-based dispositions change during a preparation program. A systematic approach to tracking change, or the lack thereof, using valid and reliable instruments of varying item types, can help faculty determine if candidates’ dispositions are positive and improving at the individual student and group levels. Pre-existing affective and cognitive data for six cases were analyzed for evidence of consistency with the 10 interstate teacher assessment and support consortium or InTASC standards. Dispositions improved as the cases progressed through their programs.